Penilaian Pemeringkatan Koperasi Di Kabupaten Lingga Periode Tahun 2019 - Yudith Dwi Astuti; Eka Setiajatnika; Trida Gunadi (Universitas Koperasi Indonesia, 2022)
The purpose of this study was to assess the ranking of cooperatives in measuring the performance and development of service-oriented cooperatives. Through this assessment effort, it is hoped that internally cooperatives will be able to improve performance and learning (capacity building) to reinforce their identity as pillars of the people's economy. This research method is a type of inequality evaluation model research (the discrepancy evaluation model). This study evaluates the performance of nine cooperatives in the Lingga Regency, Riau Islands Province in 2019 using the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 21/Per/M.KUKM/IX/2015. The results of the performance assessment and ranking of the nine cooperatives are: 1) Primkopal Lanal obtained a total score of 266, with a Qualified Enough qualification and ABB Predicate; 2) KPRI Handayani Elementary School Teachers (Lingga Utara) obtained a total score of 286, qualified enough and predicated ABB; 3) The Anugerah Cooperative of SMPN I Singkep obtained a total score of 265, qualified with Enough qualifications and the ABB predicate; 4) The Linga Lestari Mangrove Cooperative obtained a total score of 263, Qualified Enough qualification and ABB Predicate; 5) The Mekar Lestari Cooperative (Singkep Pesisir) obtained a total score of 275, with a Qualified Enough qualification and ABB predicate; 6) The Singkep Sejahtera Cooperative (West Singkep) obtained a total score of 266, qualified with Sufficient Quality and ABB Predicate; 7) KSU Prima Bermahligai (West Singkep) obtained a total score of 264, Qualified Enough qualification and ABB Predicate; 8) KSU Gender Maritime obtained a total score of 261, Qualified Enough qualification and ABB Predicate; and 9) Pasar Bersama Maju Cooperative obtained a total score of 301, Qualified Enough qualification and ABB Predicate.